Teologia tekstu Rdz 32, 25-32 w świetle jego literackiej struktury - Szwarc, Urszula (The Biblical Annals, 2017)
The paper consists of two parts. The first one discusses the text of Gen 32, 25:32, whereas the second one depicts the literary composition of the verses under analysis. The composition allows us to believe that its leading idea is the truth about God the Creator and Sovereign Ruler of man.